1998
DOI: 10.1002/j.1552-4604.1998.tb04370.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Dose Pharmacokinetics and Pharmacodynamics of Alprazolam in Elderly and Young Subjects

Abstract: The pharmacokinetics and pharmacodynamics of the benzodiazepine anxiolytic alprazolam (1 mg orally) were compared between young and elderly healthy volunteers. Eight young subjects (mean age 29.8 years) and eight elderly volunteers (mean age 68.4 years) received oral placebo and alprazolam (1.0 mg) in a randomized, double-blind, single-dose crossover study. In the elderly subjects, plasma concentrations were higher, although not significantly so, than in young volunteers 0.25, 0.5, and 0.75 hours after dosage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
4
21
0
2
Order By: Relevance
“…Given that alprazolam metabolism has not been shown to vary across the menstrual cycle (Kirkwood et al 1991), andCiraulo et al (1996) reported that alprazolam plasma levels were similar in FHP and FHN females following a single dose of alprazolam, we did not feel that collecting plasma levels in the present study was justified. However, changes in both electrophysiological activity and DSST performance have been shown to be correlated with alprazolam plasma levels (Kaplan et al 1998). Further, in a recent study (SaridSegal et al 2000), alprazolam plasma levels tended to be higher in FHP individuals than FHN individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Given that alprazolam metabolism has not been shown to vary across the menstrual cycle (Kirkwood et al 1991), andCiraulo et al (1996) reported that alprazolam plasma levels were similar in FHP and FHN females following a single dose of alprazolam, we did not feel that collecting plasma levels in the present study was justified. However, changes in both electrophysiological activity and DSST performance have been shown to be correlated with alprazolam plasma levels (Kaplan et al 1998). Further, in a recent study (SaridSegal et al 2000), alprazolam plasma levels tended to be higher in FHP individuals than FHN individuals.…”
Section: Discussionmentioning
confidence: 94%
“…46 Peak alprazolam plasma concentrations occur approximately 2 hours after oral administration. [47][48][49][50] Based on these pharmacokinetic data, D-amphetamine and alprazolam were administered simultaneously to assess behavioral effects across peak plasma levels of both drugs.…”
Section: Drug Administrationmentioning
confidence: 99%
“…Performance on the test was a significant variable in discriminant function analyses of long-and short-term schizophrenics (Royer & Janowitch, 1973). Substitution tests also have utility in demonstrating the effects of alcohol and medications on performance (e.g., Cameron, Sinclair, & Tiplady, 2001;Kaplan et al, 1998;Mattila, Aranko, Mattila, & Paakkari, 1994). Despite the wide application of substitution tests there is no clear agreement on what the test measures.…”
Section: Introductionmentioning
confidence: 96%